Trade Unions and the Burden of the Public Debt - Erling Steigum (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper looks at intergenerational welfare effects of increased public debt when union power in pay bargaining generates structural unemployment. Debt policy works through capital accumulation as well as the price of a fixed asset that is owned by the old generation. Under a reasonable condition, the debt burden on future generations from postponement of the labor tax is larger than in the case of no union power. Under this condition, increased union power also reduces the consumption of future generations.
Keywords: 330; public debt; trade unions; intergenerational welfare